Subjective's interactions on legal and regulatory's speech:analysis of the figure of the Judge of Law - Haret, Florence Cronemberger (Laboratório Editorial FCL-UNESP, 2009)
The law, as representation of a large communication process, use the legal language to build it own reality – prescriptive system of actions. On this process, the legal text is, create and spread the image of a corpus, a voice, a character of the person that enunciate. And his/her presence is presented as an effect of meaning, designed by and in the subjective’s roles taken in pairs in the speech. To that extent, enunciator, narrator and interlocutor are different levels of producers and products of legal stated. The first incorporated in the enunciation; the second, in the instance of the enunciation enunciated; and the third installed in the enunciate. These interactions will be located in different typesof text in the law system: laws; sentences; contracts; witness testimony ... It is in the chain of prescription of the legal rule that will be noticed the presence of the subject, in all these enunciation’s instances, pointing to the inevitable syncretism of roles between subjects in legal discourse.